Climate‐Driven Change in the North Atlantic and Arctic Oceans Can Greatly Reduce the Circulation of the North Sea. Issue 21 (5th November 2018) - Holt, Jason; Polton, Jeff; Huthnance, John; Wakelin, Sarah; O'Dea, Enda; Harle, James; Yool, Andrew; Artioli, Yuri; Blackford, Jerry; Siddorn, John; Inall, Mark
Abstract: We demonstrate for the first time a direct oceanic link between climate‐driven change in the North Atlantic and Arctic Oceans and the circulation of the northwest European shelf seas. Downscaled scenarios show a shutdown of the exchange between the Atlantic and the North Sea and a substantial decrease in the circulation of the North Sea in the second half of the 21st century. The northern North Sea inflow decreases from 1.2–1.3 Sv (1 Sv = 10 6  m 3 /s) to 0.0–0.6 Sv with Atlantic water largely bypassing the North Sea. This is traced to changes in oceanic haline stratification and gyre structure and to a newly identified circulation‐salinity feedback. The scenario presented here is of a novel potential future state for the North Sea, with wide‐ranging environmental management and societal impacts. Specifically, the sea would become more estuarine and susceptible to anthropogenic influence with an enhanced risk of coastal eutrophication. Plain Language Summary: Little is known about how climate change might impact the long‐term circulation of shelf seas. In this paper, we use a high‐resolution shelf sea model to demonstrate how end‐of‐century changes in the wider ocean can lead to a substantial reduction in the flow of water from the North Atlantic into the North Sea. This, in turn, reduces the circulation of this sea, which becomes more influenced by rivers and less by oceanic waters. River water generally contains higher levels of nutrients, and our simulations show that this future scenario leads to enhanced levels of phytoplankton growth in local regions of the North Sea. This may lead to undesirable disturbances to the marine ecosystems, such as depletion of oxygen near the seabed. The reduced circulation would also disrupt the transport of larvae around the sea and lead to increased retention of pollutants. The reduction in circulation arises from several causes relating to increased density layering at the continental shelf edge, changes in the large‐scale ocean circulation and salinity, and disruption of the density‐driven circulation of the North Sea. By exploring these novel future scenarios, we emphasize the need to understand better the many ways climate change can influence the marine environment and its ecosystems. Key Points: Potential end‐of‐century scenarios of dramatically reduced North Sea inflow and circulation are demonstrated by downscaling experiments This reduction is traced to increased shelf‐slope salinity stratification and modified North Atlantic and Arctic circulation and salinity The North Sea then becomes more estuarine, with some regions of substantially enhanced nutrient content and primary production